Makna Teologi Sebagai Kepala Gereja Terhadap Ibadah Dalam Umat Kristiani - Asriyati Nome (Jurnal Pendidikan Agama dan Teologi, 2024)
In human life on earth, humans cannot be separated from the image of their Creator. An intimate relationship with the Creator achieved through worship can make human life more meaningful and understand the true purpose of human life. This intimate relationship is more easily felt through the physical atmosphere that people feel and then understand and understand, so that people understand God's true authority in their lives. With this understanding, a person can begin to live a part of his life that is not in vain and leads to spiritual and worldly success. The need for a church forum that is able to convey God's majesty and His protective power gives rise to the demand to present a church forum that can arouse the interest of its people through an atmosphere that supports worship activities. The church is a place where the congregation can worship Almighty God by understanding and experiencing the heavenly atmosphere directly through the physical atmosphere as well as praising and worshiping when worshiping. The church is designed to enhance the quality of the congregation's typical ministry that focuses on praise and worship. The interior arrangement through its architectural elements has been processed in such a way that it can provide a supportive atmosphere, that is, it can reflect the atmosphere of joy in the lives of people who believe in God.